1997
DOI: 10.1083/jcb.137.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Subnuclear Trafficking of Glucocorticoid Receptors In Vitro: Chromatin Recycling and Nuclear Export

Abstract: We have used digitonin-permeabilized cells to examine in vitro nuclear export of glucocorticoid receptors (GRs). In situ biochemical extractions in this system revealed a distinct subnuclear compartment, which collects GRs that have been released from chromatin and serves as a nuclear export staging area. Unliganded nuclear GRs within this compartment are not restricted in their subnuclear trafficking as they have the capacity to recycle to chromatin upon rebinding hormone. Thus, GRs that release from chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 92 publications
6
55
0
Order By: Relevance
“…52,53 It is noteworthy that tyrosine phosphatase inhibitors stimulated chromatin-released GR export from nuclei, which suggests the involvement of a phosphotyrosine system in the regulation of nuclear GR export. 54 In agreement with these data, it has been reported that treatment of A549 cells with TNF-␣ targeted GR, possibly by phosphorylation, to remain in cytoplasm. 55 However, TNF-␣ increased the GR number and glucocorticoidinduced transcriptional activity of the GR in L-929 mouse fibroblast, 56 which is in contradiction with the above data.…”
Section: Discussionsupporting
confidence: 77%
“…52,53 It is noteworthy that tyrosine phosphatase inhibitors stimulated chromatin-released GR export from nuclei, which suggests the involvement of a phosphotyrosine system in the regulation of nuclear GR export. 54 In agreement with these data, it has been reported that treatment of A549 cells with TNF-␣ targeted GR, possibly by phosphorylation, to remain in cytoplasm. 55 However, TNF-␣ increased the GR number and glucocorticoidinduced transcriptional activity of the GR in L-929 mouse fibroblast, 56 which is in contradiction with the above data.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the seemingly oppositional effects of vanadate on GR that we report are not unique to our cells or receptor, suggesting that the signal mechanism which mediates the vanadate stimulus is conserved, at least between human, simian and murine cells. That vanadate can actually stimulate tyrosine phosphorylation while modulating GR action has been shown by DeFranco and co-workers [34]. In this work, molybdate or vanadate treatment of permeabilized cells caused both an increase in overall tyrosine phosphorylation of proteins within the nucleus and stimulation of nuclear export of hormone-free receptors.…”
Section: Discussionsupporting
confidence: 65%
“…Digitonin-permeabilization and hypotonic buffer extraction of 3617.4 cells were performed essentially as described (19). Briefly, cells were rinsed with PBS and then transport buffer (20 mM Hepes-KOH, pH 7.8͞110 mM potassium acetate͞5 mM sodium acetate͞2 mM magnesium acetate͞1 mM EGTA).…”
Section: Methodsmentioning
confidence: 99%
“…We set out to develop an in situ assay for nuclear protein mobility that would maintain the transcriptional competence of isolated nuclei yet provide a system where the effects of specific subnuclear trafficking factors could be assessed. Previously, we used a modified hypotonic buffer extraction of digitonin-permeabilized cells (24) to reveal differential nuclear affinities of ligand-bound vs. unliganded nuclear GR (19). This technique was applied herein to mouse 3617.4 and 5953 cell lines, which contain an integrated copy of a GFP-GR and -PR chimera, respectively, under the control of a tet-regulated promoter (17,25).…”
Section: In Situ Assay To Assess Gr Mobility In Transcriptionally Commentioning
confidence: 99%